Improving Hypertension Control in Primary Care With the Measure Accurately, Act Rapidly, and Partner With Patients Protocol: Results at 6 and 12 Months. Issue 6 (December 2018) - Egan, Brent M.; Sutherland, Susan E.; Rakotz, Michael; Yang, Jianing; Hanlin, R. Bruce; Davis, Robert A.; Wozniak, Gregory
Abstract : Better blood pressure (BP; mm Hg) control is a pivotal national strategy for preventing cardiovascular events. Measure accurately, Act rapidly, and Partner with patients (MAP) with practice facilitation improved BP control (<140/<90 mm Hg) from 61.2% to 89.8% during a 6-month pilot study in one primary care clinic. Current study objectives included evaluating the 6-month MAP framework in 16 Family Medicine Clinics and then withdrawing practice facilitation and determining whether better hypertension control persisted at 12 months since short-term improvements often decline by 1 year. Measure accurately included staff training in attended (intake) BP measurement and unattended automated office BP when intake BP was ≥140/≥90 mm Hg. Act rapidly (therapeutic inertia) included protocol-guided escalation of antihypertensive medications when office BP was ≥140/≥90 mm Hg. Partner with patients (systolic BP decline/therapeutic intensification) included shared decision making, BP self-monitoring, and affordable medications. Study data were obtained from electronic records. In 16 787 hypertensive adults (mean, 61.2 years; 54.1% women; 46.0% Medicare) with visits at baseline and first 6 months, BP control improved from 64.4% at baseline to 74.3% ( P <0.001) at 6 and 73.6% ( P <0.001) at 12 months. At the first MAP visit, among adults with uncontrolled baseline BP and no medication changes (n=3654), measure accurately resulted in 11.1/5.1 mm Hg lower BP. During the first 6 months of MAP, therapeutic inertia fell (52.0% versus 49.5%; P =0.01), and systolic BP decreased more per therapeutic intensification (−5.4 to −12.7; P <0.001). MAP supports a key national strategy for cardiovascular disease prevention through rapid and sustained improvement in hypertension control, largely reflecting measuring accurately and partnering with patients. Abstract : Supplemental Digital Content is available in the text.